Salmonella Saintpaul Outbreak: Export and Trade Economic Impact - Campo, Nohelia Castro-del; Chaidez, Cristóbal; Medrano-Félix, José A.; Heredia, J. Basilio; León-Félix, Josefina; Aguilar, Gustavo González; Zavala, J. Fernando Ayala (IntechOpen, 2012)
None